Produção de sementes de Lupinus albescens para recuperação de áreas degradadas por arenização - Dorneles, Fabiana de Oliveira (2009)
The objective of this work was to evaluate the best sowing time allied to appropriate fertilization levels for the development of Lupinus albescens, seeking seeds production, in sandy area, and also to verify the adaptation of this specie in soils with different clay content from the place of origin. For this, an experiment was carried out in São Francisco de Assis county, on Typic Quartzipsamments soil with experimental units distributed in random blocks design, with subdivided plots, constituted of three seeding times, seven fertilization levels and four replications. Fertilizing management was accomplished with base in the recommendation stipulated for the cultivation of Lupinus spp, according to SBCS (2004), being tested fractions of the dose to supply the crop nutritional needs (phosphorus and potassium) for the place, being applied 0, 25, 50, 75, 100, 125 and 150% of the recommended dose, with the sowing performed in May, June and July of 2008. To test the effect of the clay content on the growing of L. albescens, experimental units were carried out in random blocks design in three different places, with four replications, being the treatments the different soils types: Typic Quartzipsamments (6% of clay), Paleudalf (16% of clay) and Haplortox (48% of clay). At 150 days after seeding, were verified the plants survival index, height of plants and number of legumes per plant. After harvesting, were determined seeds yield and medium weight of 100 seeds. The observation of the results were restricted to the experiments implanted in the months of May and June, developed on sandy soil (degraded area), because L. albescens seeded in July didn t complete its development, fact that also happened in the experiment implanted on Haplortox and Paleudalf, and in this last there wasn t seeds germination. For the plants survival results, it was verified that there was low population of surviving plants, however the seeding in May showed higher medium of survival plants than the seeding done in June, with no statistical differences among the doses of applied fertilizer in the same time. The largest average of height of plants was verified in the treatment of 75% of the fertilizer dose recommended for Lupinus spp, with the crop seeding in May, as well as the results of number of legumes per plant and grain yield, regarding 27,9 legumes for plant and 351,33 kg ha-1 of grains on soil degraded. The verification of the development of L. albescens on soils with different clay content showed that this plant only adapts to sandy soils, with high content of sand, because were obtained 31,65 kg ha-1 of grains on cultivation in degraded soil, differing statistically of the null production on the other soil types. Besides, is concluded that May is the most appropriate time to seed L. albescens, allied to the application of 75% of the fertilizer dose recommended for the cultivation of Lupinus spp, seeking seeds production.